2023
DOI: 10.1007/s00431-023-04973-7
|View full text |Cite
|
Sign up to set email alerts
|

Diseases associated with prematurity in correlation with N-terminal pro-brain natriuretic peptide levels during the early postnatal life

Abstract: The aim of this observational study was to investigate the influence of different typical preterm diseases on NT-proBNP serum levels in the early postnatal period of life of a preterm infant. NT-proBNP levels of 118 preterm infants born ≤ 31 weeks GA were determined at the first week of life, after 4 ± 1 weeks of life, and at a corrected gestational age of 36 + 2 weeks. Relevant complications with a possible influence on NT-proBNP values in the first week of life such as early neonatal infection, hemodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been strongly suggested that various complications of prematurity may affect NT-proBNP levels, namely hemodynamically significant patent ductus arteriosus (HsPDA), pulmonary hypertension, BPD, retinopathy of prematurity, inflammation, sepsis and possibly necrotizing enterocolitis and intraventricular haemorrhage (IVH) [ 26 ]. Bronchopulmonary dysplasia is considered a neonatal form of chronic inflammatory pulmonary disorder with characteristic clinical and radiographic presentation, affecting newborns born prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…It has been strongly suggested that various complications of prematurity may affect NT-proBNP levels, namely hemodynamically significant patent ductus arteriosus (HsPDA), pulmonary hypertension, BPD, retinopathy of prematurity, inflammation, sepsis and possibly necrotizing enterocolitis and intraventricular haemorrhage (IVH) [ 26 ]. Bronchopulmonary dysplasia is considered a neonatal form of chronic inflammatory pulmonary disorder with characteristic clinical and radiographic presentation, affecting newborns born prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential not to solely rely on them for making a diagnosis, because measured levels can be influenced by factors such as age (both gestational and postnatal), fluid status, systemic hypertension, and shunt volumes [ 61 ]. There is also an indication that pro-BNP values may be influenced by other complications of prematurity, including retinopathy of prematurity, sepsis, necrotizing enteropathy, and intraventricular hemorrhage [ 63 ]. BNP has a half-life of approximately 20 min, and NT-proBNP has a half-life of 2 h; therefore, both tests are limited in their ability to reflect the steady state [ 64 ].…”
Section: Challenge #1: Screening and Confirmationmentioning
confidence: 99%